2014
DOI: 10.1590/0104-1428.1738
|View full text |Cite
|
Sign up to set email alerts
|

Treatments of jute fibers aiming at improvement of fiber-phenolic matrix adhesion

Abstract: Abstract:Composites based on a thermoset phenolic matrix and jute fibers were prepared and characterized. The fibers were alternatively treated with ionized air or aqueous alkaline solution (mercerization) with the aim of introducing changes in the morphology, dispersive component of surface free energy, g S D (estimated by Inverse Gas Chromatography, IGC) and the acid/base character of their surfaces, shown by their AN s /DN s ratio (estimated by IGC), and their degree of crystallinity. The final objective wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
(30 reference statements)
0
6
0
4
Order By: Relevance
“…Alkaline treatment causes a decrease of the lignin and hemicellulose contents and increases the fiber surface roughness, improving tensile strength and Young's modulus [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Alkaline treatment causes a decrease of the lignin and hemicellulose contents and increases the fiber surface roughness, improving tensile strength and Young's modulus [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Such result could be attributed to the fact that the fibers extremities act as stress risers and crack initiation sites, decreasing the material flexural strength [6] . In this case, the higher fiber-to-matrix volume ratio contributed to this decrease in flexural strength, since there are more stress risers points [34,35] . It was also observed that the incidence of gamma radiation decreased the mechanical strength of the materials, because of the degradation on fibers caused by radiation [7] , which was evidenced by the surface fractures observation.…”
Section: Resultsmentioning
confidence: 96%
“…A utilização de resinas lignina-aldeído ou lignina-fenol-aldeído como substituintes da resina fenólica convencional podem ser utilizadas tanto na preparação de compósitos de matriz termorrígida usando fibras lignocelulósicas como bagaço de cana de açúcar (PAIVA; FROLLINI, 2001), fibra de juta RAZERA et al, 2014), fibra de curauá (TRINDADE et al, 2008), fibra de sisal (RAMIRES et al, 2010;DE OLIVEIRA et al, 2017) como reforço estrutural, quanto na preparação de painéis de madeira: MDF, madeira compensada, painéis de partículas orientadas, painéis de palha, dentre outros (YANG et al, 2015;GHORBANI et al, 2017).…”
Section: Lignina: Fonte De Anéis Aromáticos Fenólicosunclassified
“…A MFS utilizada no presente estudo como agente de reforço de matriz termorrígida fenol-formaldeído foi caracterizada em termos de sua composição química após processo de extração ciclohexano: etanol (1:1) (Tabela 13). , 2006;HASSAN et al, 2010;RAZERA et al, 2014;DE OLIVEIRA et al, 2015).…”
Section: Composição Químicaunclassified
See 1 more Smart Citation